1998
DOI: 10.3928/0147-7447-19980101-14
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cold Compression Dressings After Total Knee Replacement: A Randomized Controlled Trial

Abstract: This prospective, controlled study compared cold compressive dressings with wool and crepe in the postoperative management of patients undergoing total knee replacement (TKR). Forty TKR patients were assessed for blood loss, pain, swelling, and range of motion. Patients in the cold compression group had less blood loss through suction drainage (982 ml versus 768 ml). A higher proportion of patients in the treatment group did not require blood transfusion postoperatively. Mean opiate requirements were lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…The benefits of cryotherapy following TJA are conflicting. Whereas some studies showed improved pain levels, [77][78][79] reduced blood loss, [78][79][80][81] and increased range of motion, [79][80][81] other studies showed no differences in these parameters. 80,[82][83][84] A recent meta-analysis found that the potential benefits of cryotherapy may not be clinically significant to justify its use.…”
Section: Cryotherapymentioning
confidence: 99%
“…The benefits of cryotherapy following TJA are conflicting. Whereas some studies showed improved pain levels, [77][78][79] reduced blood loss, [78][79][80][81] and increased range of motion, [79][80][81] other studies showed no differences in these parameters. 80,[82][83][84] A recent meta-analysis found that the potential benefits of cryotherapy may not be clinically significant to justify its use.…”
Section: Cryotherapymentioning
confidence: 99%
“…However, the clinical outcomes on ROM have been equivocal. Some studies have shown a benefit [4][5][6][7] , whereas others have demonstrated no difference [8][9][10][11] . One of the reasons for these controversial results may be different procedures of cryotherapy used in different studies.…”
mentioning
confidence: 99%
“…At others, treatment was applied on the basis of 'clinical need', with the majority of patients still receiving the treatment. The application of post-operative cryotherapy is a practice supported by Shelbourne and Wilkens (1990), Levy and Marmar (1993), Leutz and Harris (1995) and Webb et al (1998), who documented the benef its of cryotherapy following efficacy trials. However, Healy et al (1994) report no objective benef it in range of movement, swelling, blood loss or analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…There are no standardized clinical guidelines relating to cryotherapy management in terms of the method of application, or on which postoperative day therapy is started, or the frequency with which it is applied. However, despite this apparent confusion, there is evidence in the literature that cryotherapy can be effective and present experience suggests that patients derive some objective and subjective benefits from it (Shelbourne and Wilkens, 1990;Webb et al, 1998;Leutz and Harris, 1995). Enloe et al (1996) investigated physiotherapists' methods of treating TKR and observed a multitude of different treatment programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation